Analisis Kepadatan Lapangan Dengan Metode Sand Cone Pada Pembangunan Jalan Lingkar Utara Lamongan - Bagas Dwi Putra W.; Muhammad Riski Faizal; Muhammad Ridho Hanafi; Surya Fadli Purwanto; Dika Ayu Safitri (Jurnal Kendali Teknik dan Sains, 2024)
The location of the road studied is the northern ring road which is still in the form of a compacted pavement layer. With this road, it can reduce traffic jams in the city and divert heavy vehicles. Field density analysis was carried out on the North Ring Road in Lamongan district using the Sand Cone method to obtain soil water content values ​​on the road. The work procedure carried out is determining the weight of the sand, the weight of the soil, the grade water, dry soil density, and field density. The testing point was carried out at 152 different points for every 25 meters, namely from STA 0+000 to STA 3+800. The results showed that the average soil water content was 19.0%, and the soil density was 96.98%. According to the requirements of SNI 03-2008-1992, the recommended soil density value is 95%. From the results of the tests that have been carried out it can be concluded that the density The soil in the field meets the specified soil density requirements because the average density in the field on road pavement is 96.98%.